827: The Chronicon Salernitanum on the Muslim Conquest of Sicily (Transmediterranean History, 2019)
The Chronicon Salernitanum holds an important account on the beginning of the Muslim conquest of Sicily. It explains how this had been caused by a certain Euphemios, the commander of Western Sicily: his betrothed had allegedly been abducted by a Greek rival on the island. In an act of revenge, Euphemios entered into an alliance with the Aġlabid ruler of Ifrīqiya in order to punish him. This article contrasts the Latin narrative with extant Arabic and Greek sources, and contextualises them both with regard to the historical events as well as to the historiographical endeavour of explaining and potentially excusing such a large-scale conquest.
Keywords: Aghlabids; Byzantium; Greek Christians; sexual violence; gender relations; Sicily; Arabic-Islamic expansion; treason; collaboration; North Africa; Southern Italy